Scintillation SE detector for variable pressure scanning electron microscopes - Jirák, J; Nedela, V; Cernoch, P; Cudek, P; Runstuk, J (Journal of microscopy, 2010)
We present results obtained with a new scintillation detector of secondary electrons for the variable pressure scanning electron microscope. A detector design is based on the positioning of a single crystal scintillator within a scintillator chamber separated from the specimen chamber by two apertures. This solution enables us to decrease the pressure to several Pa in the scintillator chamber while the pressure in the specimen chamber reaches values of about 1000 Pa (7.5 Torr). Due to decreased pressure, we can apply a potential of the order of several kV to the scintillator, which is necessary for the detection of secondary electrons. Simultaneously, the two apertures at appropriate potentials of the order of several hundreds of volts create an electrostatic lens that allows electrons to pass from the specimen chamber to the scintillator chamber. Results indicate a promising utilization of this detector for a wide range of specimen observations.